Cosmological Entropy and Seeking of Genesis of Time - Konduru, Rakesh Teja (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Influenced with symmetry of entropy and time in nature, we tried to invoke relation between entropy and time in space-time with new dimension. And also provided how Hubbles constant related with entropy of universe. Discussed about how entropy of universe behaves at different temperatures and at different time values of universe. We showed that age of universe is equivalent to Hubbles constant. And showed how naturally entropy arrives from the manipulations in gravity from Einsteins equation 00. And from these results we concluded that universe is isotropic, homogeneous with negative space curvature i.e. K= -1 but not flat K=0 (which doesn't explain acceleration and deceleration of universe). From these results of gravity, entropy, temperature and time we discussed the genesis of time. And proposed that at absolute zero temperature universe survives as a superconductor and that particular temperature is called as Critical Absolute Temperature (TAB). And genesis of time occurs at first fluxon repulsion in the absolute zero temperature of universe.